Efektivitas Peran BAPPEDA Dalam Perencanaan Pembangunan Labuhan Batu - Tri Agustin Ritonga; Hendra Harmain (Pusat Riset dan Inovasi Nasional, 2023)
Regional development planning involves the Regional Development Planning Agency, which is an institution that supports regional development within its area of ​​authority. Bappa's responsibility is to provide technical regulations for services and development strategies. The purpose of this research is to determine the impact of performance on Bappa Medan. Research that focuses on the effectiveness of this role is descriptive and qualitative. Interviews with workers in the regional equipment and infrastructure sector were used as a data collection method. Secondary data was obtained from books and articles discussing the impact of Bafeda in Medan. Based on the research results, Bapeda's performance in Medan has not been completely successful.